HALAL AWARE COMMUNITY MODEL BASED ON MASJID: ANALYSIS OF LEVEL OF CARE, AWARENESS, AND SATISFACTION OF MUSLIM TOURISTS IN MAKASSAR - Muhammad Nusran; Hasibuddin Hasibuddin; St.Nurhayati Azis; Andi Darmawangsa; Ardi Ardi; Agussari Henny; Yan Herdianzah; Nur Ihwan Safutra (Center for Study and Journal Management FTI UMI, 2023)
This study aims to assess the success of a halal-conscious community model based on the Masjid in Makassar by examining the level of awareness and satisfaction of local communities and Muslim tourists. The quantitative method with a survey approach was used, and 300 local community respondents and 200 Muslim tourist respondents were randomly selected as the study sample. The data were collected using questionnaires that consist of questions about respondent characteristics, the level of awareness and concern for halal products and services, and satisfaction and recommendations for the halal-conscious community model. The collected data were analyzed using descriptive statistical and factor analysis methods to identify the factors that affect the success of the halal-conscious community model. The validity and reliability of the research instruments were tested using content validity and Cronbach's alpha method, respectively. The results showed that the local community respondents had a high level of awareness and concern for halal products and services, with an average score of 3.8 out of 5, indicating that the halal-conscious community model has successfully increased the awareness of local communities. Furthermore, Muslim tourists showed high levels of satisfaction with the halal-conscious community model, with an average score of 4.1 out of 5, indicating that the model has provided halal products and services that meet their needs. In conclusion, the halal-conscious community model based on the Masjid in Makassar has been successful in increasing the awareness and satisfaction of both the local community and Muslim tourists